Cytotoxic Potential of Biogenic Zinc Oxide Nanoparticles Synthesized From Swertia chirayita Leaf Extract on Colorectal Cancer Cells - Berehu, Hadgu Mendefro; S, Anupriya; Khan, Md Imran; Chakraborty, Rajasree; Lavudi, Kousalya; Penchalaneni, Josthna; Mohapatra, Bibhashee; Mishra, Amrita; Patnaik, Srinivas (Frontiers in Bioengineering and Biotechnology, 2021)
Chemotherapy side effects, medication resistance, and tumour metastasis impede the advancement of cancer treatments, resulting in a poor prognosis for cancer patients. In the last decade, nanoparticles (NPs) have emerged as a promising drug delivery system. Swertia chirayita has long been used as a treatment option to treat a variety of ailments. Zinc oxide nanoparticles (ZnO-NPs) were synthesized from ethanolic and methanolic extract of S. chirayita leaves. ZnO-NPs were characterized using UV-visible spectroscopy, FTIR, SEM, HRTEM and XRD. Its anti-cancer activities were analyzed using cytotoxicity assays (MTT assay & acridine orange (AO) staining) and qRT-PCR using colorectal cancer (CRC) cells (HCT-116, and Caco-2) and control cells (HEK-293). The ZnO-NPs synthesized of ethanolic extract of S. chirayita has an average size of 24.67nm whereas of methanolic has 22.95nm with the spherical shape. MTT assay showed NP’s cytotoxic potential on cancer cells (HCT-116, and Caco-2) when compared to control cells (HEK-293). The IC50 values of ethanolic and methanolic extract ZnO-NPs for HCT-116, Caco-2, and HEK-293 were 34.356 ± 2.71 and 32.856±2.99 µg/ml, 52.15±8.23 and 63.1±12.09 µg/ml, and 582.84±5.26 and 615.35±4.74 µg/ml respectively. Acridine orange staining confirmed the ability of ZnO-NPs to induce apoptosis. qRT-PCR analysis revealed significant enhanced expression of E-Cadherin whereas reduced expression of Vimentin and CDK-1. Altogether, these results suggested anti-cancer properties of synthesized ZnO-NPs in CRC.